Challenges and Strategies for Quantification of Drugs in the Brain: Current Scenario and Future Advancement. (2nd January 2022) - Pyaram, Akhila; Rampilla, Madhuri; Deore, Jayshri; Sengupta, Pinaki
Abstract: The site of action of centrally acting drugs lies inside the brain and therefore, needs to reach the brain to exert their therapeutic efficacy. Discovery and development process of such types of drugs demands their quantification in brain to establish the dose, study pharmacokinetics, pharmacodynamics, and optimize the overall efficacy. Moreover, some drugs of other categories also have potential to cross blood–brain barrier resulting in various adverse events by acting centrally. However, the collection of a matrix to analyze the amount of drugs present in brain is highly challenging. In this review, we have summarized different bioanalytical strategies to quantitate drugs inside the brain. A detailed discussion on various in vivo and in vitro techniques for monitoring drugs inside the brain has been incorporated. In addition, various sampling techniques have been discussed in brief with case studies. Therefore, this review can guide the researcher to choose appropriate bioanalytical techniques for analyzing drugs in brain depending upon the specific need and quantification threshold considering the commonly associated difficulties of the methods.